(untitled) (Pedagogy of Higher and Secondary Education, 2011)
Some problems of formation professional communicative competence of future economists were highlighted in the article. Competitive content and its functions are being researched by optimization of studying Economy at a higher educational economic establishment, upgrading the students in economy educational level.